¿Importa la ley? : la respuesta de un juez al movimiento de la escuela crítica del Derecho - Rubin, Alvin B. (2006)
Fil: Rubin, Alvin B. Louisiana State University. Paul M. Hebert Law Center. Baton Rouge, Estados Unidos